2008
DOI: 10.1111/j.1440-1827.2008.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma arising in von Meyenburg complexes: Report of four cases

Abstract: Although von Meyenburg complexes (VMC) are largely considered to be innocuous, neoplastic transformations have been described. The present report describes four cases of cholangiocarcinoma (CC) occurring on a background of VMC. The patients were all male and aged 69, 59, 68 and 75 years, respectively. While two patients were asymptomatic, the other two had a history of colon cancer. Radiologically the tumors measured 3, 4, 4.5 and 10 cm and were well enhanced from the arterial to delayed portal phase. Microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…VMCs are thought to result from persistence of the embryonic ductal plate and are generally adjacent to portal areas [1] . Multiple case reports showed exist of VMCs with histologic evidence of transformation to cholangiocarcinoma, showing benign, hyperplastic and dysplastic epithelium with adjacent progression to invasive carcinoma [7,8,38,39] . These lesions are fairly common with prevalence of 5.6% in adults and 0.9% of children in one autopsy series, and are especially prevalent in patients with adult polycystic kidney disease or congenital hepatic fibrosis [40] .…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…VMCs are thought to result from persistence of the embryonic ductal plate and are generally adjacent to portal areas [1] . Multiple case reports showed exist of VMCs with histologic evidence of transformation to cholangiocarcinoma, showing benign, hyperplastic and dysplastic epithelium with adjacent progression to invasive carcinoma [7,8,38,39] . These lesions are fairly common with prevalence of 5.6% in adults and 0.9% of children in one autopsy series, and are especially prevalent in patients with adult polycystic kidney disease or congenital hepatic fibrosis [40] .…”
Section: A B C Dmentioning
confidence: 99%
“…No intraepithelial or intraductal preneoplastic, dysplastic or neoplastic lesions have been demonstrated in the small bile ducts or ductules [5] . Von Meyenburg complex (VMC) is suggested to be a possible premalignant lesion of ICCs due to the occasional association of VMC with ICCs and reports of VMC-like cystic ICCs [6][7][8] . Progression of bile duct adenoma (BDA) to ICC has also been reported [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Tohme-Noun et al [1] found elevated serum levels of gamma-glutamyltranspeptidase (GGT) that could not be explained by another disease in 4 out of 11 patients with histologically proven hamartomatosis. The prevalence of biliary hamartomas has been estimated at 5.6% in adults and 0.9% in children [1,2]; the rate increases with age and chronic liver disease [7]. Biliary hamartomas can be confused with metastases, microabscesses, cysts, biliary adenomas, dilated bile ducts [4], cirrhosis [8,9], granulomatous hepatitis [8] and cystadenocarcinoma [10].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic examination reveals that they are composed of a variable number of disorganised irregular tiny bile ducts immersed in fibrocollagenous stroma that may be hyalinised [11]. The ductal structures have a variable degree of dilation, can contain viscous bile [2] and do not communicate with the normal terminal bile ducts [5]. When the ducts dilate, they may coalesce in cystic cavities with intracavitary persistence of surrounding connective tissue forming endocystic polypoid projections [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation